The mere wife - Headley, Maria Dahvana, 1977- (Farrar, Straus and Giroux, 2018)
From the perspective of those who live in Herot Hall, the suburb is a paradise. Picket fences divide buildings<U+2015>high and gabled<U+2015>and the community is entirely self-sustaining. Each house has its own fireplace, each fireplace is fitted with a container of lighter fluid, and outside<U+2015>in lawns and on playgrounds<U+2015>wildflowers seed themselves in neat rows. But for those who live surreptitiously along Herot Hall<U+2019>s periphery, the subdivision is a fortress guarded by an intense network of gates, surveillance cameras, and motion-activated lights. For Willa, the wife of Roger Herot (heir of Herot Hall), life moves at a charmingly slow pace. She flits between mommy groups, playdates, cocktail hour, and dinner parties, always with her son, Dylan, in tow. Meanwhile, in a cave in the mountains just beyond the limits of Herot Hall lives Gren, short for Grendel, as well as his mother, Dana, a former soldier who gave birth as if by chance. Dana didn<U+2019>t want Gren, didn<U+2019>t plan Gren, and doesn<U+2019>t know how she got Gren, but when she returned from war, there he was. When Gren, unaware of the borders erected to keep him at bay, ventures into Herot Hall and runs off with Dylan, Dana<U+2019>s and Willa<U+2019>s worlds collide.